The Hypermasculine and Ubersexual Men in the Harlequin Novels of the 1980s and 2000s - Sari M.R.D Soedibio; Jenny M. Djundjung (Institute of Research and Community Outreach - Petra Christian University, 2013)
Harlequin novels are so popular that Harlequin romance emerges as a genre. Unlike on the heroines, there are scarcely any studies or works on the heroes, thus, I want to focus my study on the heroes of Harlequin Romance. By analyzing using the Male Sex Role in the 1980s and themes of masculinity in the 2000s, I will prove that there are four types of ideal men in the 1980s Harlequin novels whose characteristics originated from the ideal men in the society at that time, the Hypermasculine men with extreme masculinity and avoidance of any feminine sides. I will also prove that there are three types of ideal men in the 2000s Harlequin novels whose characteristics are in accordance with the Ubersexual men’s, the ideal men in the society in 2000s having positive characteristics of traditional manliness with some “feminine“ characteristics. The reason behind these changes is because of the changes in the heroines and the characteristics of men in the society in time and these push for the changes in the heroes. As a publisher, Harlequin’s goal is the highest selling rate, thus, they adjust to the market’s demand.